Implementasi Metode Keteladanan pada Pembelajaran Akhlak di SMP Muhammadiyah Boarding School Tarakan - Luthfi Anis Muadzin; Romelah Romelah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the implementation of exemplary methods in moral learning, especially in the material of speaking manners at Muhammadiyah Boarding School Tarakan. The method in this study uses a qualitative approach, with the type of case study research. Data collection techniques with observations, interviews and documents on teachers and students. The results of the study show that the exemplary method applied in moral learning has a positive impact on changing student behavior, especially in terms of speaking politely and respecting others. Learning is carried out through the opening, core, and closing stages that emphasize the importance of speaking manners in daily life. The teacher acts as the main role model by showing speaking manners that are in accordance with the teachings of Islam. Although the exemplary method has proven to be effective, the biggest challenge lies in the istiqomama of students in applying speaking manners in daily life.